Plant extract of noni (Morinda citrifolia) as growth promoters of broilers (Research, Society and Development, 2020)
In this study were evaluated the use levels of Noni extract (Morinda citrifolia) on intestinal histomorphometry, nutritional metabolism, biochemical serum profile, and performance of broilers. Completely randomized design with six treatments and six replicates of ten male commercial Cobb chicks were used in each replicate. The broilers was spraid treatments with addition to the diet of 150, 300, 450, and 600 ppm of noni extract, beyond negative and positive controls, without or with 25 ppm of tylosin, respectively. Feed intake, weight gain, feed conversion of broilers at 7, 21, and 35 days old were evaluated at the performance test. The nutrient metabolization was determined using the method of total excreta collection. At 7, 21, and 35 days old, the two birds per replicate was collected, after blood collection, the birds were euthanized to histomorphometry of the intestinal segments. Data were subjected to regression analysis, considering linear and quadratic models for variance analysis. Subsequently, treatments with Noni levels were compared with the negative and positive controls, using the F test for orthogonal contrasts. The inclusion of noni in the diet of plant extracts does not change the performance, carcass characteristics, biometrics of the digestive system, intestinal histomorphometry, and biochemical serum profile of broilers, in relation to diet without growth promoter. Therefore, although it is not hepatotoxic, noni extract did not improve growth in broilers.